Dinamika Ekologi Masyarakat Pesisir Pantai Kili-Kili (Studi Kasus Konservasi Penyu Desa Wonocoyo Trenggalek) - Saputri, Vindyana Cipta; Zahid, A (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The existence of modernity has given rise to industrialism which has resulted in environmental degradation. More than that, the emergence of degradation is also caused by several factors such as demographic factors, economic factors carried out by society, internal changes in society and market dynamics. Not all environmental degradation or changes have a negative impact, environmental changes provide economic-demographic opportunities and create changes in attitudes, values and norms in society. This article aims to explain the ecological dynamics of the coastal community of Kili-Kili Beach which is located in Wonocoyo Village, Panggul District, Trenggalek Regency. The research was conducted using qualitative methods with data collection techniques through observation and interviews. The research results show that poor natural interactions and natural transformation that occurred in Wonocoyo Village have given rise to environmental consequences that have an impact on environmental degradation. Environmental changes that occur in Wonocoyo Village occur due to natural and human factors. Apart from that, demographic factors are also one of the causes of environmental changes in Wonocoyo Village, with the increasing number of residents in Wonocoyo Village causing an increase in human needs for nature. Natural changes in Wonocoyo Village also provide demographic economic opportunities for coastal communities and create changes in attitudes, values and norms in the community so that they succeed in making Wonocoyo Village a superior and advanced village based on environmental conservation.